2003
DOI: 10.1080/00288330.2003.9517152
|View full text |Cite
|
Sign up to set email alerts
|

A recent sponge,Pleroma aoteaKelly ("Order” Lithistida: Family Pleromidae), in the late Eocene Ototara Limestone of Otago, New Zealand

Abstract: Pleroma aotea Kelly ("Order" Lithistida: Family Pleromidae) from deep-water seamounts and banks off northeastern New Zealand, and are significant in that they represent a stratigraphic range for the species of more than 35 million years. The presentday distribution of P. aotea, limited to silica-rich deeper waters, is in marked contrast to the relatively shallow warm water volcanic environments occupied during the Palaeogene. This restriction, and that of related lithistid sponges to silica-rich deeper waters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
17
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
4
17
0
Order By: Relevance
“…Lévi (1960) considered a possible affinity of Vetulina with Crambe (Poecilosclerida: Crambeidae) due to the fact that both possess sphaeroclonar desmas. Kelly et al (2003) found that the desmas of the fossil species V. oamaruensis Hinde and Holmes (1892) resembled the desmas of a species of Crambe from northern New Zealand, suggesting conspecifity. We consider the affinity of desmas between these two genera to be the result of convergence, as molecular studies have indicated that Crambe is very distant from Vetulina (Schuster et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Lévi (1960) considered a possible affinity of Vetulina with Crambe (Poecilosclerida: Crambeidae) due to the fact that both possess sphaeroclonar desmas. Kelly et al (2003) found that the desmas of the fossil species V. oamaruensis Hinde and Holmes (1892) resembled the desmas of a species of Crambe from northern New Zealand, suggesting conspecifity. We consider the affinity of desmas between these two genera to be the result of convergence, as molecular studies have indicated that Crambe is very distant from Vetulina (Schuster et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The most common bioclasts are bryozoan fragments. Fossil-rich beds are common, containing whole brachiopods (Gage 1957), bivalve molluscs (Beu & Maxwell 1990), larger bryozoan fragments (Brown 1952), echinoderms, serpulids, octocorals, barnacles (Buckeridge 1983), lithistid sponges (Kelly et al 2003), whale bones (Fordyce 1980), penguin bones (Fordyce & Jones 1990), foraminifera (Gage 1957;Hornibrook 1961;Edwards et al 1991), ostracodes (Edwards et al 1991) and rhodoliths (Lee et al 1997). The Oamaru Diatomite, a member of the Ototara Limestone, has an exceedingly rich diatom fauna (Edwards et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Antarctic isocrinids were collected with detailed sedimentological information, enabling accurate environmental and temporal placement. In addition to previously described fossil occurrences [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] , this substantial new body of data indicates that the Southern Hemisphere was an important shallow water isocrinid province during the Paleogene. The data presented herein provides conclusive evidence that the migration of stalked isocrinids from shallow to deep water did not occur at the same time all over the world.…”
mentioning
confidence: 55%
“…3 Distribution of shallow marine stalked crinoids in the Cenozoic of the Southern Hemisphere. Newly discovered and described fossils along with those previously described from Antarctica [32][33][34][35][36] , New Zealand [37][38][39][40][41][42][43][44][45][46] , South America 47 , and Australia 48 33 Rasmussen 1979 32 Zinsmeister et al 1989 36 Malumian & Olivero 2005 47 Eagle 2004 39 Eagle 1993 37 Feldmann & Maxwell 1990 45 Stilwell et al 1994 38 This study…”
mentioning
confidence: 98%
See 1 more Smart Citation